Uneven distribution of inorganic pollutants in marine air originating from ocean-going ships. (March 2017) - Bencs, László; Horemans, Benjamin; Buczyńska, Anna Jolanta; Van Grieken, René
Abstract: The distribution of mass, water-soluble inorganic salts and mineral elements of size-segregated aerosols (PM1, PM2.5-1 and PM10-2.5 ), precursor gaseous pollutants, black carbon, and nanoparticles (10–300 nm size range) at the Southern Bight of the North Sea has been studied. The concentrations of air pollutants peaked over shipping lanes, open-water anchorage areas and frequently navigated waters, due to the presence of mobile emission sources. A considerable decrease in air pollutant levels was seen when diverting from these marine areas towards remote or coastal banks. These findings showed the rapid dispersion of pollutants in the marine air. The nano-aerosol count, originating from ocean-going ships, peaked at lower average aerodynamic diameters (e.g., ≈28 nm) than those, observed from low-displacement vessels (45–50 nm, e.g., for fishing boats). The average diameter of nano-PM depended also on weather conditions, e.g., it was higher (≈50 nm) in air of higher humidity. Graphical abstract: Highlights: Marine and coastal air pollutants of the Southern North Sea were monitored. Size-segregated aerosols, precursor gases, BC and nano-particles were mapped. Pollutant levels generally peaked over frequently navigated waters. Slow atmospheric dispersion of ship emission related pollutants were found. Nano-particle distributions showed ship (fuel) type dependent characteristics. Abstract : The concentration distribution of several ship exhaust plume related atmospheric inorganic pollutants, including nano-aerosols, has been mapped in high resolution at the Southern Bight of the North Sea.